A Comparative Systematic Literature Review of Policies Enhancing Women’s Electoral Participation in Indonesia, India, and Canada - Sapardiyono; Al Fauzi Rahmat; Galih Bagas Soesilo; Elita Laili Hanifah (Yayasan Sinergi Kawula Muda, 2026)
This study examines comparative policy approaches to enhancing women’s electoral participation in Indonesia, India, and Canada through a Systematic Literature Review (SLR). The study addresses a gap in comparative gender policy literature by synthesizing cross-national evidence regarding how institutional design, affirmative action mechanisms, and socio-political contexts shape women’s electoral participation across different democratic systems. Unlike prior studies that mainly emphasize single-country analysis, this review develops a comparative framework for evaluating the effectiveness and limitations of women’s electoral participation policies. The review employed the PRISMA protocol using articles indexed in Scopus, Web of Science, and Google Scholar published between 2014 and 2025. Inclusion criteria covered peer-reviewed English-language studies discussing women’s electoral participation, quota policies, political representation, and electoral reform in Indonesia, India, or Canada. Following screening, eligibility assessment, and duplicate removal, 32 articles were selected for analysis. The comparison focused on policy design, institutional implementation, and substantive outcomes of women’s participation and representation. The findings reveal substantial differences in policy effectiveness across the three countries. Indonesia’s 30% legislative quota policy has increased women’s descriptive representation, yet substantive participation remains constrained by patriarchal political culture and weak party support. India’s reservation policy at the local governance level has strengthened grassroots political participation, although proxy representation and socio-cultural barriers persist. Canada demonstrates comparatively stronger outcomes through integrated gender-sensitive reforms, leadership development, and institutional support mechanisms. The study concludes that quota policies alone are insufficient without broader institutional support, inclusive political structures, and socio-cultural transformation to achieve substantive gender equality in electoral participation.